2018
DOI: 10.1186/s13568-018-0659-3
|View full text |Cite
|
Sign up to set email alerts
|

Statistical modelling for optimized lyophilization of Lactobacillus acidophilus strains for improved viability and stability using response surface methodology

Abstract: The awareness regarding use of probiotics for health benefits has created a huge market worldwide. The use of probiotic cultures and its success in commercial scale is relying on the techniques employed to ensure that the potential cultures with desired functional activity are stable and viable for longer period. The present study was undertaken to statistically evaluate the effect of lyoprotectant in the suspension media containing sucrose and reconstituted skim milk on the viability of Lactobacillus acidophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…On the contrary, the L. agilis strain seemed to be more tolerant against a physical force, since no significant changes were observed between cryo-protectants or non-protected feed samples. This corresponds to a report by Sadguruprasad and coworkers (2018) who found highly variable and strain-dependent storage effects on microorganisms [62]. However, the designated protectants in this study benefited the stability of both strains from short-term to mid-term storage when mixed and stored with feed.…”
Section: Discussionsupporting
confidence: 88%
“…On the contrary, the L. agilis strain seemed to be more tolerant against a physical force, since no significant changes were observed between cryo-protectants or non-protected feed samples. This corresponds to a report by Sadguruprasad and coworkers (2018) who found highly variable and strain-dependent storage effects on microorganisms [62]. However, the designated protectants in this study benefited the stability of both strains from short-term to mid-term storage when mixed and stored with feed.…”
Section: Discussionsupporting
confidence: 88%
“…strains were more stable at the temperature of 4 °C than in room temperature. Moreover, it is worth underlining that the effects of storage may be highly variable and strain dependent (Turuvekere Sadguruprasad and Basavaraj 2018 ). Similar results were noticed in the presented study.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of these compounds in the lophilization of lactobacilli has been obtained by other researchers (Otero et al, 2007;Juárez Tomás et al, 2009;Li et al, 2011). A medium containing a minimum amount of sucrose (1.2%) in skim milk (6%) maintains the viability of lyophilized cultures for two years (Turuvekere Sadguruprasad & Basavaraj, 2018). With the use of sucrose and betaine, it was found that only sucrose has cryoprotective properties in the freezing of lactic acid bacteria L. coryniformis (Bergenholtz et al, 2012).…”
Section: Selection Of Technological Regime and Cryoprotectormentioning
confidence: 97%